The unyielding - Laurenston, Shelly (Laurenston, Shelly. Call of the Crows., 2017)
In order to save the other clans, angry Viking Stieg Engstrom joins forces with Erin Amsel, a pain-in-the-neck Crow, but the two must resist each other's charms in order to complete the mission.